2022
DOI: 10.1093/schbul/sbac065
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine (NAC) in Schizophrenia Resistant to Clozapine: A Double-Blind, Randomized, Placebo-Controlled Trial Targeting Negative Symptoms

Abstract: Background and Hypothesis Clozapine is the most effective antipsychotic for treatment-resistant schizophrenia, yet a significant proportion of individuals on clozapine continue to experience disabling symptoms, despite being treated with an adequate dose. There is a need for adjunct treatments to augment clozapine, notably for negative and cognitive symptoms. One such potential agent is the glutathione precursor N-acetylcysteine (NAC). Study D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…These findings were consistent withYolland et al (2020) at the ≤24 weeks mark, but after 24 weeks, Yolland et al observed significant improvement in negative symptoms and PANSS total scores with NAC treatment. Our study, which included a 52-week RCT(Neill et al, 2022) comparing the efficacy of 2 g/d NAC and placebo in 84 patients with clozapine-refractory schizophrenia, produced opposing results. Clozapine-refractory schizophrenia was defined as patients who had received at least three different chemical classes of antipsychotics and at least F I G U R E 3 Meta-analysis of N-acetylcysteine versus placebo for patients with psychotic disorder: total score as measured by the positive and negative syndrome scale (PANSS).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…These findings were consistent withYolland et al (2020) at the ≤24 weeks mark, but after 24 weeks, Yolland et al observed significant improvement in negative symptoms and PANSS total scores with NAC treatment. Our study, which included a 52-week RCT(Neill et al, 2022) comparing the efficacy of 2 g/d NAC and placebo in 84 patients with clozapine-refractory schizophrenia, produced opposing results. Clozapine-refractory schizophrenia was defined as patients who had received at least three different chemical classes of antipsychotics and at least F I G U R E 3 Meta-analysis of N-acetylcysteine versus placebo for patients with psychotic disorder: total score as measured by the positive and negative syndrome scale (PANSS).…”
mentioning
confidence: 89%
“…NAC was used as an adjunct therapy to antipsychotics (clozapine (Neill et al, 2022), risperidone (Farokhnia et al, 2013;Zhang et al, 2015)) in all studies. One study included treatment-resistant patients taking clozapine (Neill et al, 2022). The duration of the study ranged from 8 to 52 weeks, with four RCTs lasting 8 weeks, one 12 weeks, one method and were judged as low risk of bias, three trials were judged as unclear risk of bias because they did not report the random method clearly.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…The effect on disorganized thought is relevant in prognostic terms since disorganization domain scores may be predictors of treatment-resistant schizophrenia [ 317 ]. In a placebo-controlled RCT for TRS patients with persistent psychotic symptoms treated with clozapine, NAC as adjuvant therapy was not shown to significantly improve cognitive symptoms or quality of life in TRS patients [ 318 ]. Furthermore, a recent meta-analysis inferred that the recommendation in routine clinical practice for NAC treatment in schizophrenia might be premature despite its antioxidant potential.…”
Section: Antioxidants: a Possible Add-on Strategy In The Treatment Of...mentioning
confidence: 99%
“…Neill et al 11 described an investigator-initiated, industryindependent, moderately large (n = 84), well-designed, well-conducted, well-analyzed, 52-week RCT of NAC (2 g/d) in schizophrenia patients with persistent symptoms that were refractory to at least 3 classes of antipsychotic drugs as well as to ≥ 6 months of treatment with their current medication, clozapine. The study was conducted in medical centers in 4 cities in Australia.…”
Section: Rct: Nac Augmentation Of Clozapinementioning
confidence: 99%